Transcriptional profiling analysis providing insights into desiccation tolerance mechanisms of the desert moss Syntrichia caninervis - Yang, Ruirui; Li, Xiaoshuang; Yang, Qilin; Zhao, Mingqi; Bai, Wenwan; Liang, Yuqing; Liu, Xiujin; Gao, Bei; Zhang, Daoyuan (Frontiers in Plant Science, 2023)
Syntrichia caninervis is a desiccation tolerant moss and is the dominant bryophyte found in biological soil crusts in the Gurbantunggut desert. In this study, we assessed the transcriptome profiles of S. caninervis gametophytes during dehydration-rehydration (D-R) process (across nine time points) using Illumina sequencing. In total, 22489 transcripts were identified, including 5337 novel transcripts, that mapped to the reference genome. A total of 12548 transcripts exhibited significant alterations in the D-R samples compared with the control samples. The differentially expressed transcripts (DETs) possessed several enriched Gene Ontology terms, such as “water stress response”, “oxidation-reduction process”, “membrane metabolism”, “photosynthesis”, and “transcription factor activity”. Moreover, during early dehydration stress, the DETs were significantly enriched in stress-related pathways from the Kyoto Encyclopedia of Genes and Genomes, such as “phenylpropanoid biosynthesis”, “alpha-Linolenic acid metabolism”, and “fructose and mannose metabolism”. Photosynthesis-related transcripts (e.g.,ScPsa H, ScRubisco, and ScLhcb1) were inhibited during the dehydration treatment and significantly accumulated during the late rehydration period. Most transcripts from the late embryogenesis abundant proteins (LEA) and early light-inducible protein (ELIP) families strongly accumulated at the late dehydration stage. These pathways were positively correlated with the content changes of absolute water content and Fv/Fm values, alongside peroxidase and superoxide dismutase activities. Seven transcription factor families, including AP2-ERF, bHLH, G2-like, MYB, NAC, WRKY, and bZIP, were enriched in DETs during D-R treatment. This study is the first transcriptome analysis using the S. caninervis genome for gene annotation and multigroup D-R treatment points. Our results demonstrated the detailed dynamic changes in the transcriptome of S. caninervis during the D-R process; these results also improved understanding of desiccation tolerant plants adaptations to desiccation stress at the transcription level, and provided promising gene resources for transgenic crop breeding.